Parent and Teacher Perspectives on Factors Decreasing Participation in School-Based Vision Programs. (3rd May 2020) - Vongsachang, Hursuong; Friedman, D. S.; Inns, A.; Kretz, A. M.; Mukherjee, M. R.; Callan, J.; Wahl, M.; Repka, M. X.; Collins, M. E.
ABSTRACT: Purpose : To examine factors decreasing participation in school-based vision programs from parent and teacher perspectives. Methods : We conducted 41 semi-structured focus groups (20 parent groups, 21 teacher/staff groups), at 10 Baltimore and 11 Chicago public elementary and middle schools offering school-based vision programs. School-based vision programs provided vision screening, eye exams, and eyeglasses if needed. Focus groups ranged in size from 2–9 participants (median = 5). Sessions were recorded, transcribed, and coded through an iterative process to develop themes using inductive analysis. Results : Ninety parents and 117 teachers/staff participated. Participants identified five major factors decreasing participation in school-based vision programs: (1) challenges with the consent form, including distribution, collection, and literacy and language barriers; (2) having existing eye care; (3) misunderstandings about the program, especially related to cost and insurance; (4) difficulty raising parental awareness of the program; and (5) certain attitudes towards vision, eye care, and school-based programs, including low prioritization of eye care, mistrust of the program, fear of sharing private information, not believing their child needs glasses, and reluctance accepting 'subsidized' services. Conclusion : Parents and teachers identified important structural barriers to participation (i.e., consent form challenges and low parental awareness) and specific reasons for non-participation (i.e., attitudes, misunderstanding of the program, existing eye care) in school-based vision programs. Effective strategies are needed to facilitate return of consent forms and promote awareness of school-based vision programs among parents. Programs should also target services towards those currently without access to eye care and increase awareness about paediatric vision needs.